Temperament, parenting, mental disorders, life stressors and help-seeking behavior of Asian adolescent suicide attempters: A case control study - Wong, John Chee Meng; Chang, Christel Lynne; Shen, Liang; Nyein, Nyein; Loh, Adrian Seng Wei; Yap, Natalie Huijing; Kroneman, Leoniek Mirjam; Feng, Lei; Tan, Chay Hoon (Frontiers in Psychiatry, 2022)
Purpose The need to elucidate risk factors for adolescent suicide is urgent, as suicide consistently ranks among the top causes of death globally. Understanding suicide risk factors could inform more effective interventions. Previous studies have identified certain risk factors associated with suicide, but there is a paucity of research among adolescent and multi-ethnic Asian populations. Materials and methods This case-control study sampled 13-to-19-year-old Asian adolescents who had attempted suicide (N = 60) and controls (N = 58) matched by age, ethnicity and gender at group-level (73.7% female). Life stressors, temperament, parenting style, mental health conditions and help-seeking behavior were examined. Results All domains of life stress apart from emerging adult responsibility were higher among cases than controls, especially home life, peer pressure and romantic relationships. Suicide attempters tended to avoid new situations, be less adaptable to changes, have a negative outlook and irregular sleep-wake cycle. Additionally, they perceived their parents to be significantly more aggressive, neglecting, rejecting and cold, while parents’ perceptions of their own parenting were only significantly different in the domain of parental neglect. Cases were more likely to exhibit disorders of disruptive behavior, eating, mood, anxiety, symptoms of schizophrenia and experience of disturbing events. Significant differences were also found for 10 out of 12 Axis II disorders, particularly borderline, depressive, and avoidant personality disorder traits. No significant case-control differences were found regarding overall rates of help-seeking. Conclusion Findings from this study may help in suicide prevention efforts through more tailored interventions.